P4.024 Do New Media Affect Adolescent Sexual Attitudes and Behaviours? A Systematic Review. (13th July 2013) - Smith, L Watchirs; Guy, R; Degenhardt, L; Richters, J; Robbins, S; Kaldor, J; Lumby, C; Skinner, R; Liu, B
Abstract : Introduction: There is considerable public concern that new media (including the Internet and mobile phones) could be exposing young people to high levels of sexual content and may impact risky behaviour and/or risk for sexually transmissible infections. Methods: The review was conducted in accordance with the PRISMA guidelines. Medline, EMBASE and PsychINFO were searched to the end of August 2012. Articles were included if they described the statistical association between exposure to sexual content in new media (viewing or engaging) and sexual attitudes or behaviours in young people (defined as < 25 years). Results: There were 3834 articles identified, and five met the inclusion criteria: all were cross-sectional designs (four convenience samples), with the largest study containing 6054 participants. In four studies the exposure was viewing sexually explicit websites (SEW); a range of outcomes were assessed however each outcome variable was only measured in one or two of the included studies. Viewing SEW was significantly associated with: first intercourse < 15 years of age, ever having a sexual partner, > 1 partner in last 3 months, multiple lifetime partners, unprotected sex at last sex, drug and alcohol use at last sex, acceptance of casual sexual relationships, having casual sexual relationships, notions of women as sex objects, and approval of extra-marital sex. "Sexting" (sending or receiving sexual texts) was the exposure in the fifth study and was associated with ever having unprotected sex. Conclusion: The relationship between SEW and sexual behaviours and attitudes was inconsistent. Engagement with sexual media appeared to be associated with markers of higher sexual interest and/or activity, but study size, methodological approach and inconsistencies in outcome measures prevented us from drawing conclusions regarding causality. No study explored associations with positive aspects of sexual development (e.g. sexual communication, sexual assertiveness, relationship quality). Further research in this emerging area is needed.